(untitled) (Journal of Educational Sciences, 2019)
Globalization is a process which affects all areas of social life, including education. The impact of globalization is widely discussed and there are different opinions whether globalization leads to diver- gence or convergence of educational systems. The key research question: are we getting closer to each other or are we choosing different trajectories of educational development? The object of our study is the process of educational development in post-socialist countries. The aim of the study is to reveal the impact of globalization on educational change in the region. The method used in the study is second- ary analysis of statistical and research data. Our hypothesis is based on the assumption that the process of globalization determined the application of similar reform trends in educational sectors of the nation states. However, different level of educational development and specific historical, social and cultural contexts lead to a growing differentiation of the educational models of the countries in the region. In other words, application of similar approaches led to different outcomes in the domain of education. The data analysis showed that the differences within the post-socialist world are growing and the countries, instead of forming a single group, are moving towards different pre-established educational models. Анaлиз дaнных покaзaл, что рaзличия в постсоциaлистическом мире рaстут, Key words: globalization, systems of education, post-socialist countries.